فعالية تطبيق طريقة القواعد والترجمة لتعزيز مهارة قراءة كتاب التراث في معهد باب الرضا العزيزية - Saadah, Nelis; Rivensky, Rizka (Institut Agama Islam Negeri Lhokseumawe, 2023)
This article is entitled the implementation of the qawa'id and translation methods in improving the reading ability of the yellow book for grade 2 students at Dayah Babur Ridha Al-Aziziyah, with the background of the problem being that students who study the yellow book have weaknesses in understanding sentence divisions. So they find it difficult to read and interpret the words in the yellow book. Therefore, researchers want to find out the ability of students to understand the division of sentences contained in the yellow book by using the qawa'id and translation methods. The purpose of this study is to find out the students' ability to read the yellow book at Dayah Babur Ridha Al-Aziziyah before and after using the qawa'id and translation methods and to find out whether the application of the qawa'id and translation methods can improve the students' ability to read the book yellow at Dayah Babur Ridha Al-Aziziyah. The research method used by researchers is a quantitative approach with the One Group Pretest and Posttest Design method where researchers only use 1 class as a population and a sample consisting of 21 students. To obtain research data results, researchers used the SPSS application to analyze research data in the form of descriptive analysis, normality test and paired sample t test. The results of the research obtained can be concluded that the application of the qawa'id and translation methods in learning the yellow book is to improve reading skills more effectively and this method can improve the ability of students to read the yellow book at Dayah Babur Ridha Al-Aziziyah